“The Merchandise Has Appeared on the Market”: The Typology of Plunderers, Schemes of Illegal Realization, and Legal Practice in Soviet Lithuania (1945–1947) - Indrišionis, Darius (Lietuvos istorijos studijos, 2021)
This research focuses on plunder from variuos co-operative or state institutions (mostly those which had belonged to the Ministry of Internal Trading or the Unity of Co-operatives of Lithuanian SSR) in the first post-war years (1945–1947) in the Lithuanian SSR. The primary source for this article is comprised by 54 criminal cases from the archive of the Supreme Court of the Lithuanian SSR. Cases used in this study were chosen based on one important criteria: that there were not only acts of plunder but also the realization of stolen goods. This would most likely be achieved by selling the goods through various marketplaces (looking from the Soviet point of view, the plundered items belonged to the black market anyway – even if the market activities were not forbidden). Also, the practices of punishment applied in the cases of plunderers and speculators are analyzed. The research shows that even in the very first years of the post-war period, illegal economic processes were widespread in Soviet Lithuania. Plunderers were hitting the Soviet economy hard – despite the harsh practice of punishment, the Soviet government would lose tens of millions of rubles in the Lithuanian SSR each year.